Base Coach — Negligent Supervision. Issue 4 (4th May 2021) - Sawyer, Tonya L.
Abstract: Plaintiff injured his ankle sliding into third base during a junior varsity baseball game. John Suk was the JV baseball coach for Bound Brook High School and was also acting as the third base coach during the game in which plaintiff was injured. Plaintiff filed suit alleging defendants "negligently" and "carelessly" supervised the JV baseball game.